2021
DOI: 10.1007/s11222-021-10061-3
|View full text |Cite
|
Sign up to set email alerts
|

Constrained parsimonious model-based clustering

Abstract: A new methodology for constrained parsimonious model-based clustering is introduced, where some tuning parameter allows to control the strength of these constraints. The methodology includes the 14 parsimonious models that are often applied in model-based clustering when assuming normal components as limit cases. This is done in a natural way by filling the gap among models and providing a smooth transition among them. The methodology provides mathematically well-defined problems and is also useful to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In our application study, for example, we have observed a large similarity between SPRM and enetLTS, which overshadows the ranking results of RSK-means. As K-means can be seen as a special case of tclust 14 , a more flexible robust clustering approach which is particularly designed to fit clusters with different scatters and weights, it would for instance be interesting to replace trimmed k-means by this more general approach blueor even more advanced versions 44 , 45 in future applications.…”
Section: Discussionmentioning
confidence: 99%
“…In our application study, for example, we have observed a large similarity between SPRM and enetLTS, which overshadows the ranking results of RSK-means. As K-means can be seen as a special case of tclust 14 , a more flexible robust clustering approach which is particularly designed to fit clusters with different scatters and weights, it would for instance be interesting to replace trimmed k-means by this more general approach blueor even more advanced versions 44 , 45 in future applications.…”
Section: Discussionmentioning
confidence: 99%
“…Gaussian distribution is the normal distribution, and model-based clustering is an iterative method to fit a set of datasets into clusters [29]. This method works in three steps: First, randomly choose Gaussian parameters and fit them to a set of data points.…”
Section: Fig 4 Dbscan Cluster Visualizationmentioning
confidence: 99%
“…A model-based algorithm may locate clusters by constructing a density function that reflects the spatial distribution of data points, and it also automatically decides on the number of clusters based on standard statistics, considering noisy data or isolated points, resulting in robust clustering methods [39]. Typical model-based clustering methods include statistical methods (e.g., COBWEB, CLASSIT, and AutoClass) or neural network methods (e.g., competitive learning and self-organizing feature maps) [40,41]. Model-based clustering algorithms are computationally complex and slightly inadequate for handling large-scale data sets.…”
Section: Current Status Of Research Applications Of Data Processing A...mentioning
confidence: 99%